Comparisons and influence temperature humidity index to dairy cow productivity based on farm altitude - Bambang Kholiq Mutaqin; Didin Supriat Tasripin; Lia Budimulyati Salman; Iin Susilawati; Ujang Hidayat Tanuwiria1 (Fakultas Pertanian Universitas Majalengka, 2024)
This study aimed to determine the differences and effects of the Temperature Humidity Index (THI) on dairy cows’ productivity in West Java based on differences in farm altitude. Categorization based on area altitude can be divided into low altitude (<700 m asl), moderate (700-1000 m asl), and high (> 1,000 m asl). The parameters observed were body size, body weight, and milk production which were supplemented by environmental conditions namely temperature and humidity. The method used is a survey and direct observation by simple random sampling of animals. The results showed differences in environmental conditions, namely temperature and humidity in each dairy farm with different altitudes. Meanwhile, the performance of milk production is relatively the same even though variations in the performance of body measurements and weight of dairy cows in each region. It can be concluded that heat environmental conditions with high THI can cause cows to suffer from heat stress so that productivity decreases.